Sistem Informasi Lokasi Sekolah Terdekat dengan Jejaring Sosial Sekolah dan Orang Tua Siswa Berbasis Web (Studi Kasus Paud Dan Sd Di Kota Malang) - Aisy Nurmalasarri (Jurnal Jaringan Telekomunikasi, 2017)
This information system aims to find the closest distance from the parents' house to the school in Malang by looking at the location map that has been provided on the web. Making this web-based information system using the programming language PHP and MySQL and AMPPS to create the required database on the web. Social networks are created in the form of profile processing, photo galleries, and message processing. The search for location points is determined by the admin and the user's coordinates can be known automatically and the results obtained from the calculation of the distance on the web or manually are obtained from the SDN Jatimulyo 4 with a distance of 92 meters on the web and 0.1 km on the calculation manually using a spido meter, the closest PAUD to the user's coordinate point is TK Tadika Puri with a distance of 1.1 km on the web and 1.2 in manual calculations using a spido meter. This shows that the closest distance using google maps and manual calculations using a spido meter to search for the nearest location gets almost the same results, so the analysis of the results can be said to be a good category.